ompT encodes the Escherichia coli outer membrane protease that cleaves T7 RNA polymerase during purification. - Grodberg, J (1988)
Bacteriophage T7 RNA polymerase is stable in Escherichia coli but very susceptible to cleavage by at least one endoprotease after cell lysis. The major source of this endoprotease activity was found to be localized to the outer membrane of the cell. A rapid whole-cell assay was developed to screen different strains for the presence of this proteolytic activity. Using this assay, we identified some common laboratory strains that totally lack the protease. Genetic and Southern analyses of these null strains allowed us to conclude that the protease that cleaves T7 RNA polymerase is OmpT (formerly termed protein a), a known outer membrane endoprotease, and that the null phenotype results from deletion of the OmpT structural gene. A recombinant plasmid carrying the ompT gene enables these deletion strains to synthesize OmpT and converts them to a protease-positive phenotype. The plasmid led to overproduction of OmpT protein and protease activity in the E. coli K-12 and B strains we used, but only weak expression in the E. coli C strain, C1757. This strain-dependent difference in ompT expression was investigated with respect to the known influence of envZ on OmpT synthesis. A small deletion in the ompT region of the plasmid greatly diminishes the amount of OmpT protein and plasmid-encoded protease present in outer membranes. Use of ompT deletion strains for production of T7 RNA polymerase from the cloned gene has made purification of intact T7 RNA polymerase routine. Such strains may be useful for purification of other proteins expressed in E. coli.